DNA replication stress-induced loss of reproductive capacity in S. cerevisiae and its inhibition by caloric restriction - Weinberger, Martin (Landes Bioscience, 2013)
In many organisms, attenuation of growth signaling by caloric restriction or mutational inactivation of growth signaling pathways extends lifespan and protects against cancer and other age-related diseases. The focus of many efforts to understand these effects has been on the induction of oxidative stress defenses that inhibit cellular senescence and cell death. Here we show that in the model organism S. cerevisiae, growth signaling induces entry of cells in stationary phase into S phase in parallel with loss of reproductive capacity, which is enhanced by elevated concentrations of glucose. Overexpression of RNR1 encoding a ribonucleotide reductase subunit required for the synthesis of deoxynucleotide triphosphates and DNA replication suppresses the accelerated loss of reproductive capacity of cells cultured in high glucose. The reduced reproductive capacity of these cells is also suppressed by excess threonine, which buffers dNTP pools when ribonucleotide reductase activity is limiting. Caloric restriction or inactivation of the AKT homolog Sch9p inhibits senescence and death in stationary phase cells caused by the DNA replication inhibitor hydroxyurea or by inactivation of the DNA replication and repair proteins Sgs1p or Rad27p. Inhibition of DNA replication stress represents a novel mechanism by which caloric restriction promotes longevity in S. cerevisiae. A similar mechanism may promote longevity and inhibit cancer and other age-related diseases in humans.